Post a New Question


posted by on .

Write the following expression as one logarithm: 2logx-log4-log3+logx.
Simplify your answer.

  • PreCalc - ,


  • PreCalc - ,

    That does not seem right to me because when i graph it, they turn out different.

  • PreCalc - ,

    I am using the 3 major laws of logs

    logA + logB = log(AB)
    logA - logB = log(A/B)
    nlogA = log (A^n)

    so again...

    = log(x^2) -log4-log3 + logx
    = log((x^2)(x)/((3)(4))
    = log (x^3/12)

    You must be graphing it incorrrectly.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question